2014
DOI: 10.15274/nrj-2014-10107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Gender and Hemispheric Location on T2 Hypointensity in the Pulvinar at 3T

Abstract: SUMMARY -Pulvinar signal intensity decrease on T2-weighted images has been reported in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Iron content evaluated by T 2 * (Haacke et al, 2010) or QSM (Lim et al, 2013) appears to vary between hemispheres in some nuclei such as the pulvinar and putamen. Similarly, White et al found a higher signal ratio in the left pulvinar compared with the right on T 2 ‐weighted images and the opposite for the globus‐pallidus (White et al, 2014). A recent study has shown metabolite differences in each thalamic nuclei and between hemispheres using 1 H‐magnetic resonance spectroscopy that could be explained by cellular, functional and structural differences (Donadieu et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…Iron content evaluated by T 2 * (Haacke et al, 2010) or QSM (Lim et al, 2013) appears to vary between hemispheres in some nuclei such as the pulvinar and putamen. Similarly, White et al found a higher signal ratio in the left pulvinar compared with the right on T 2 ‐weighted images and the opposite for the globus‐pallidus (White et al, 2014). A recent study has shown metabolite differences in each thalamic nuclei and between hemispheres using 1 H‐magnetic resonance spectroscopy that could be explained by cellular, functional and structural differences (Donadieu et al, 2016).…”
Section: Discussionmentioning
confidence: 91%